Survival, response rates, and post-transplant outcomes in patients with Acute Myeloid Leukemia aged 60-75 treated with high intensity chemotherapy vs. lower intensity targeted therapy - Sahasrabudhe, Kieran; Huang, Ying; Rebechi, Melanie; Elder, Patrick; Mims, Alice; Wall, Sarah (Frontiers in Oncology, 2022)
The United States Food and Drug Administration has approved several oral, targeted therapies for the treatment of Acute Myeloid Leukemia (AML) in recent years. These agents are approved in patients with relapsed/refractory disease or as frontline therapy in patients who are ineligible for intensive chemotherapy based on age, performance status, or comorbidities. They are also being increasingly utilized frontline in patients of all ages and fitness levels through clinical trials and off label prescribing, but comparative treatment outcomes associated with intensive versus targeted therapy have not been extensively studied. We conducted a single center, retrospective analysis to address the impact of treatment intensity on survival in patients with AML aged 60-75 at diagnosis. This study included 127 patients, 73 of whom received high intensity chemotherapy at any point during treatment (any HiC) and 54 of whom received only low intensity targeted therapy (LITT only). Overall survival (OS) from treatment initiation did not differ significantly between the any HiC and LITT only groups (hazard ratio (HR) for death, 0.67; 95% CI, 0.41 to 1.09; P=0.11). The only three variables that were independently associated with superior OS were lower European Leukemia Net (ELN) risk classification, TP53 unmutated status, and receipt of transplant. Our data suggest that baseline genomic features and receipt of transplant are more important than treatment intensity in predicting survival in this patient population. They also highlight the vital role of transplant in older patients with AML regardless of treatment intensity utilized for remission induction. Larger studies are needed to further address this question, including prospective randomized trials.